Management strategy for Indian housing development waste. - Singh, Paramjeet (2022)
Housing development waste (HDW) comprises both construction and demolition waste. (define) HDW has been on the increase in India because raw materials and energy are consumed by India's housing development business due to the rise in population and the accompanying increase in the need for building/housing. Construction and demolition debris includes building material from debris and rubble from any civil structure being built or remodeled or repaired or torn down. Construction and demolition waste is among the most common types of waste generated in India. The Ministry of Environment, Forest, and Climate Change (MoEF&CC) notified the current India legislation on Waste Management Rules, 2016, on March 29th, 2016, to implement housing development and demolition waste prevention and recycling measures. However, there are insufficient tools to accelerate the development of waste recycling. As a result, it lacks resources that would allow Aggregates and Sand Manufacturing from Demolition Waste to grow more quickly and efficiently in the future. This study was conducted to determine the necessity of recycling factories that produce aggregates and sand from demolished concrete from housing development trash. Therefore, providing tools to accelerate the development of waste recycling.